Nerolidol attenuates dehydroepiandrosterone-induced polycystic ovary syndrome in rats by regulating oxidative stress and decreasing apoptosis - Turkmen, Nese Basak; Yuce, Hande; Aydin, Muhterem; Taslidere, Asli; Dogan, Aysegul; Ozek, Dilan Askin; Unuvar, Songul (Pergamon-Elsevier Science Ltd, 2023)
Aims: Although nerolidol (NRL) is a naturally occurring sesquiterpene alcohol with many pharmacological ac-tivities, its role in dehydroepiandrosterone DHEA-induced polycystic ovary syndrome PCOS is unknown. This study aims to explore the potential beneficial effects and underlying molecular mechanisms of nerolidol treat-ment on polycystic ovary syndrome.Main methods: Pre-pubertal female Sprague-Dawley rats were randomly assigned into four groups (n = 8/group); group I: control; group II: PCOS; group III: P + NRL; group IV: NRL. Biochemical parameters related to oxidative stress, inflammation, apoptosis, and hormones were estimated in the blood and ovarian tissues. Histopatho-logical, ultrastructural, and immunohistochemical analyses were performed. Bax, P53, Cas-3, and Bcl-2 gene expression levels were detected with RT-PCR. The membrane array analysis detected chemokine, cytokine, and growth factor protein profiles.Key findings: In light of the available data, it can deduce that nerolidol has a significant ameliorating effect on lipid peroxidation, oxidative stress, inflammation, histopathological damage, and apoptosis accompanying PCOS in female rats.Significance: PCOS is not only a reproductive pathology but also a systemic condition and its etiopathogenesis is still not fully understood. Since changes in PCOS have important long-term effects on health, this study evaluated the efficacy of nerolidol, a phytotherapeutic for the control of biochemical, apoptotic, histopathological, and metabolic changes.
Keywords: Nerolidol; Polycystic ovary syndrome; Oxidative stress; Apoptosis; Dehydroepiandrosterone